Parent knowledge and health behavior of children who have an accute respiratory Infection - dorce sisfiani sarimin; Semuel Tambuwun; Suci Laila Tonote (Politeknik Kesehatan Makassar, 2018)
ABSTRACTAcute Respiratory Infection (ARI) is one of the diseases that often affects children. The data found in the Manando Minanga Malalayang Public Health Center in the last year from January to December 2017 were 364 cases. One of the factors that causes ARI in children is mother's knowledge. The purpose of this study was to analyze the relationship of parental knowledge with health behaviors in children with ARI. This type of research is observational analytic conducted on 36 respondents. The measuring instrument used is a questionnaire. Hypothesis testing used Chi-Square (x²) with a significance level (α) <0.05, and a significant level> 95%. The results of the study found that from 17 respondents who had less knowledge of ARI with less behavior there were 11 respondents (30.5%) and 6 respondents (2.16%) knowledge of parents with sufficient behavior. Of the 19 respondents who had good knowledge but lack of health behavior there was 1 respondent (0.36%), good parental knowledge but enough behavior there were 7 respondents (2.52) and good parental knowledge and good behavior there were 11 respondents (30, 5). Chi-square statistical analysis obtained the value of p = value of 0,000, meaning that p = value <0.05 so that there is a relationship between parents' knowledge and health behavior in children with ARI. Suggestions for parents are expected to be willing to increase knowledge about ARI so that awareness of the importance of health for children so as not to get ARI.Keywords: ARI, Knowledge, Health BehaviorABSTRAKInfeksi Saluran Pernafasan Akut (ISPA) merupakan salah satu penyakit yang sering menyerang anak-anak. Data yang ditemukan di Puskesmas Minanga Malalayang Kota Manando satu tahun terakhir ini dari bulan Januari sampai dengan Desember 2017 sebanyak 364 kasus. Salah satu faktor penyebab terjadinya ISPA pada anak-anak adalah pengetahuan ibu. Tujuan penelitian ini adalah untuk menganalisis hubungan pengetahuan orang tua dengan perilaku kesehatan pada anak yang mengalami penyakit ISPA. Jenis penelitian ini adalah analitik observasional yang dilakukan terhadap 36 responden. Alat ukur yang digunakan adalah kuesioner. Uji hipotesa yang digunakan Chi-Square (x²) dengan derajat kemaknaan (α)<0,05, dan tingkat signifikan > 95%. Hasil penelitian ditemukan dari 17 responden yang mempunyai pengetahuan kurang penyakit ISPA dengan perilaku kurang terdapat 11 responden (30,5%) dan 6 responden (2,16%) pengetahuan orang tua dengan perilaku cukup. Dari 19 responden yang mempunyai pengetahuan baik tetapi perilaku kesehatan kurang terdapat 1 responden (0,36%), pengetahuan orang tua baik tetapi perilaku cukup terdapat 7 responden (2,52) dan pengetahuan orang tua baik kemudian perilaku baik terdapat 11 responden (30,5). Analisi statistic chi-square didapatkan nilai p=value sebesar 0,000, artinya p=value < 0,05 sehingga terdapat hubungan pengetahuan orang tua dengan perilaku kesehatan pada anak yang mengalami penyakit ISPA. Saran bagi orang tua diharapkan bersedia meningkatkan pengetahuan tentang ISPA sehingga kesadaran dalam hal pentingnya kesehatan bagi anak agar tidak sampai terkena penyakit ISPA.Kata kunci : ISPA, Pengetahuan, Perilaku Kesehatan